Positive cfDNA screening results for 22q11.2 deletion syndrome—Clinical and laboratory considerations - Soster, Erica; Dyr, Brittany; Rafalko, Jill; Almasri, Eyad; Cacheris, Phillip (Frontiers in Genetics, 2023)
Introduction: Non-invasive prenatal screening (NIPS) via cell-free DNA (cfDNA) screens for fetal chromosome disorders using maternal plasma, including 22q11.2 deletion syndrome (22q11.2DS). While it is the commonest microdeletion syndrome and has potential implications for perinatal management, prenatal screening for 22q11.2DS carries some inherent technical, biological, and counseling challenges, including varying deletion sizes/locations, maternal 22q11.2 deletions, confirmatory test choice, and variable phenotype. Materials and Methods: This study addresses these considerations utilizing a retrospective cohort of 307 samples with screen-positive 22q11.2 NIPS results on a massively parallel sequencing (MPS) platform. Results: Approximately half of the cases reported ultrasound findings at some point during pregnancy. In 63.2% of cases with diagnostic testing, observed positive predictive values were 90.7%-99.4%. cfDNA identified deletions ranging from <1 Mb-3.55 Mb, with significant differences in confirmed fetal versus maternal deletion sizes; estimated cfDNA deletion size was highly concordant with microarray findings. Mosaicism ratio proved useful in predicting the origin of a deletion (fetal versus maternal). Prediction of deletion size, location, and origin may help guide confirmatory testing. Discussion: The data shows that MPS-based NIPS can screen for 22q11.2DS with a high PPV, and that collaboration between the laboratory and clinicians allows consideration of additional metrics that may guide diagnostic testing and subsequent management.